Pathogenicity and virulence of Bipolaris bicolor on wheat, corn and sorghum - Pereira Costa Muniz, Paulo Henrique; Alves Santos de Oliveira, Thiago; Alves Duarte, Elizabeth Amélia; Rodrigues, Fabricio; Costa Carvalho, Daniel Diego (Revista Ceres, 2025)
The objective was to evaluate the pathogenicity of six strains of Bipolaris bicolor on wheat, corn and sorghum and its virulence when inoculated into healthy plant tissue of wheat under different light regimes at 25 °C. Pathogenicity was evaluated by inoculating mycelial discs in the corp leaves at 25 ºC for six days in a completely randomized design and 6x3 factorial arrangement, with the six strains of B. bicolor and three corps (wheat, corn, and sorghum). Besides, virulence was evaluated in the same conditions, excepting as follow: 6x5 factorial arrangement (six strains of B. bicolor and five photoperiods). The evaluations were performed by measuring the lesioned leaf diameter daily, which was later transformed into the lesioned leaf area (LLA). The results showed the ability of B. bicolor to infect other plant species beyod wheat, that is, the strains proved to be pathogenic on corn and sorghum leaves. Regarding its physiology, the results showed that strains such as virulence differed when inoculated on wheat leaves. The 14 h light regimen showed the greatest significant reduction in disease severity, the point from which the increase in the frequency of luminosity led to an increase in the LLA up to the 20 h light regimen.